2020
DOI: 10.3390/ma13215043
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Kinetics of Modified Basalt Glass

Abstract: As the raw material for the production of basalt continuous fibers in Sichuan, basalt glass (BG) and modified basalt glass (MBG) were prepared by the melt quenching method with the basalt and chemically modified basalt, respectively. The crystallization kinetics of BG and MBG were investigated by differential scanning calorimetry (DSC) according to Kissinger methods. The results revealed that it is difficult for both glasses to crystallize at a high temperature. In addition, the crystallization activation ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…In previous work [27], we studied the stability of Sichuan basalt glass via crystallization kinetics. The results showed that reducing the iron content can effectively improve the stability of Sichuan basalt glass, which is suitable for preparing basalt glass fiber.…”
Section: Discussionmentioning
confidence: 99%
“…In previous work [27], we studied the stability of Sichuan basalt glass via crystallization kinetics. The results showed that reducing the iron content can effectively improve the stability of Sichuan basalt glass, which is suitable for preparing basalt glass fiber.…”
Section: Discussionmentioning
confidence: 99%